Preparation and evaluation of biodegradable microspheres of methotrexate - Jayaprakash, S; Halith, S Mohamed; Firthouse, P U Mohamed; Kulaturanpillai, K; Abhijith, Abhijith; Nagarajan, M (Asian Journal of Pharmaceutics (AJP), 2014)
The objective of the present study is to prepare sustained-release methotrexate microspheres of bovine serum albumin in different ratios by the emulsion cross-linking method. The prepared microspheres were subjected to various physicochemical evaluation and in vitro release studies. The drug release from microspheres of 1:6 ratio is the most constant and prolonged drug release is diffusion followed by erosion. The characteristics of the prepared microspheres are conducive to the formulation of the sustained release drug delivery system.